IMPLEMENTASI PROGRAM BTQ DALAM MENGUATKAN NILAI-NILAI KARAKTER ISLAMI SISWA di MI BUSTANUL ULUM - Qoifatul Maulidah; Nur Khosiah; Riska Arista Sandi; Agus Sugiarto; Siti Nurhalisa SR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to reveal how the implementation of the Read-Write Al-Qur’an (BTQ) activities contributes to shaping the Islamic character of students at MI Bustanul Ulum. It focuses on the BTQ program’s implementation, the character values arising from the activities, and the factors that support and hinder the process. A descriptive qualitative approach was employed, using observation, in-depth interviews, and document analysis for data collection. Findings indicate that routine BTQ activities held every morning before the main lessons not only improve students’ Qur’anic reading and writing skills but also serve as a habituation platform for Islamic character values such as discipline, responsibility, patience, honesty, and religiosity. The activities foster a religious culture within the madrasah where Islamic values are practiced in students’ daily lives. Teachers act as guides and moral exemplars, while the headmaster ensures continuity and consistency of BTQ activities. Parental support positively influences the adoption of these habits at home. However, BTQ implementation faces several challenges, including limited time, varied student abilities in Qur’anic reading, and inadequate supporting facilities. Overall, BTQ activities at MI Bustanul Ulum are effective in shaping students’ Islamic character and have the potential to serve as a model of Qur’an-based character education for other primary madrasahs.